A Comprehensive Review of Antimicrobial Resistance against Colistin and Countermeasures (Molecular Medicine Communications, 2024)
In times of increasing antimicrobial resistance (AMR), colistin is used as a last resort against numerous gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii. Unfortunately, recent studies have shown that some species of gram-negative bacteria are becoming resistant to colistin. This has led to an increase in antimicrobial burden and limited treatment options against bacterial infections. This review highlights emerging studies aimed at optimizing the use of colistin. The frequent use of colistin for the treatment of infections has led to colistin resistance. Resistance patterns include intrinsic and acquired resistance mechanisms. The intrinsic resistance mechanism encompasses genetic modification of Lipopolysaccharide (LPS), whereas the acquired resistance mechanism involves modifications of PmrAB and PhoPQ, which alter the LPS membrane. Mutations in the CrrB, ramA, romA, ramR, and KpnEF genes, transfer of the MCR gene via plasmids, activation of efflux pumps, and capsule formation all accentuate colistin resistance. Various methods have been developed to detect resistance. Different combinatorial therapies and supramolecular traps have also been reported to be efficacious. Moreover, newer strategies and methods are required to prevent this global dilemma. This review comprehensively explains colistin resistance, its mechanisms, detection techniques, and future implications.
Keywords: Antimicrobial resistance (AMR); colistin; Gram-negative; Lipopolysaccharide; combinatorial therapies